PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA NON ASN PADA DINAS KOMINFO DAN PERSANDIAN KABUPATEN SITUBONDO DENGAN MODERASI VARIABEL MOTIVASI KERJA - Raziqin, Novanda Khayrur; Fandiyanto, Randika; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
When weighed against other production elements like money, skills, and natural resources, human resources stand out as a major player for any given firm. The three production elements are mostly driven by humans. In addition, people are the most important component in determining whether an organization will succeed or fail in reaching its objectives. The caliber of an organization's human resources greatly determines how well it accomplishes its goals and purposes. Using work motivation factors as a moderator, this research sought to examine the effects of leadership style and job satisfaction on the performance of Non-State Civil Apparatus (ASN) at Situbondo Regency's Office of Communication, Informatics, and Encoding. It is a quantitative study. This research used 30 Non-State Civil Apparatus (ASN) as its population. Saturated sampling was used as the sample method. The data analysis and hypothesis testing in this research were conducted using the Structural Equation Method - Partial Least Square (PLS-SEM). The findings of the Smart PLS 3.0 application's direct effect hypothesis testing reveal that leadership style has a substantial negative impact on performance. Performance is positively impacted by job happiness. The effect of leadership style on performance is mitigated to a large extent by intrinsic motivation at work. There is no moderating effect of work motivation on the relationship between leadership style and performance.